ANALYSIS OF THE FREE LEARNING PROGRAM ON INCREASING LITERACY IN ELEMENTARY SCHOOLS NEGERI 107439 - Desi, Sri Kusuma; Dewi, Sri Kusuma; Ray, Sukma Adelina (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2023)
This study aims to conduct an analysis of the improvement of literacy that can be done to support the government in the policy of independent study in Elementary School. Researchers conduct research by means of qualitative descriptive research using a library study approach or commonly called library research that presents the results of research in the form of analysis of a factual event that is obtaining data, materials and references from various sources such as books, articles, research results, and government regulations related to the policy of independent study and strengthening literacy in Elementary School. The Merdeka Study Program is one that is applied by the government to achieve that goal. In an effort to strengthen literacy can be done by embracing a culture of literacy in schools, the formation of a school literacy team (TLS), involving third parties, mobilizing the practical community and also conducting school programs involving participants directly educated for literacy strengthening. Literacy becomes the minimum competency or basic competence that a protégé needs to be able to learn. Merdeka learns to be the right way to improve the literacy skills that students have in fulfillment of the challenge component of the times. The results showed that in instilling literacy, reading 15 minutes before learning began, daily reading journals and graphic organizers were effective in assisting students in training literacy skills.